2013
DOI: 10.5966/sctm.2012-0116
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy to Cure Type 1 Diabetes: From Hype to Hope

Abstract: Type 1 diabetes mellitus (T1D) is a chronic, multifactorial autoimmune disease that involves the progressive destruction of pancreatic β-cells, ultimately resulting in the loss of insulin production and secretion. The goal of clinical intervention is to prevent or arrest the onset and progression of autoimmunity, reverse β-cell destruction, and restore glycometabolic and immune homeostasis. Despite promising outcomes observed with islet transplantation and advancements in immunomodulatory therapies, the need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
100
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 122 publications
0
100
0
4
Order By: Relevance
“…Diabetes Mellitus is a metabolic disorder that occurs by several factors and is characterized by high level of glucose in the blood, which can occur as a result of the autoimmune destruction of pancreatic β cells, gradually resulting in disability or partial absolute insulin in the body, or by tissue resistance to insulin action, which in both cases can lead to macro-and microvascular complications [1][2] .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes Mellitus is a metabolic disorder that occurs by several factors and is characterized by high level of glucose in the blood, which can occur as a result of the autoimmune destruction of pancreatic β cells, gradually resulting in disability or partial absolute insulin in the body, or by tissue resistance to insulin action, which in both cases can lead to macro-and microvascular complications [1][2] .…”
Section: Introductionmentioning
confidence: 99%
“…In rodents and primates, the SVF contains mesenchymal stem cells and various immune cells (Cinti 2012). The functions of the SVF cells are the subject of intensive research today, since they have the potential to impede obesity development and to resolve obesity-associated immune and metabolic dysfunctions (Chhabra and Brayman 2013;Paek et al 2014). The stem cells of the SVF differentiate into mature adipocytes and thus, the inhibition of their differentiation program can be an approach against obesity (Rosen and Spiegelman 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has increasingly focused on developing new sources of islet cells (Ramiya et al, 2000;Shapiro et al, 2006;Chhabra and Brayman, 2013;Schiesser and Wells 2014). It has been reported that fat cells, bone marrow stem cells, skin cells, and embryonic stem cells can be differentiated into cells that are able to secrete insulin (Bhonde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%